The Effect Of Duration Of Tuak Consumption On Low Density Lipoprotein (LDL) And Triglyceride (TG) Levels In The Community In Taman Bali Village - Manu, Thomas Tandi; Ananda, Dewa Ayu Putu Wiweka; Getas, I Wayan; Wiadnya, Ida Bagus Rai; Khusuma, Ari (Jurnal Analis Medika Biosains (JAMBS), 2025)
Tuak is a traditional alcoholic drink made from palm sap. Excessive alcohol consumption over a long period of time can affect lipid metabolism, increasing LDL and Triglyceride levels in the blood. Increased levels can cause cardiovascular disease. To determine the effect of the duration of tuak consumption on LDL and Triglyceride levels in the community in Dusun Taman Bali. The research used is Observational Analytical with a cross-sectional approach. The sample in this study was the community in Dusun Taman Bali who consumed Tuak for 1, 3, and 5 years with a total of 30 respondents using One Way Anova data analysis. The average LDL levels of 30 respondents with an average of 117.20 mg/dL consumed tuak for 1 year, 130.30 mg/dL for 3 years and 151.20 mg/dL for 5 years, while the average Triglyceride levels of 30 respondents who consumed Tuak for 1 year were 160.90 mg/dL, 166.60 mg/dL for 3 years and 201.10 mg/dL for 5 years. The results obtained showed a significant value of LDL levels of 0.000 while Triglyceride levels were 0.022. This means P <0.05, which means that there is an effect of the duration of tuak consumption of 1.3 and 5 years on LDL and Triglyceride levels in the community in Dusun Taman Bali.